Educational policy research groups and the research network built through scientific co-authoring production - Cleide Carvalho de Matos; Manuelle Espíndola dos Reis; Waldelicy Lacerda da Costa (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2020)
This article aims to identify the research networks built by educational policy research group leaders located in the Brazilian northern region through scientific co-authoring production. The study motivational problem is stated in the following question: What research networks do educational policy groups located in the Brazilian northern region build through co-authoring? The documentary source was the leaders Curriculum Lattes from such scientific spaces. We anchored ourselves in Bourdieu (2013; 2004; 1983) to analyze the scientific and social field. The research scope historical time encompassed the period from 1995 to 2019. The co-authoring production contributes to building the research networks that overtake the group location geographical limits. We identified that through the scientific co-authoring articles production, the leaders build research networks with different researchers and institutions that are located in other Brazilian regions, especially in the north-eastern and south-eastern regions and in foreign institutions.